Intersexuality as a potential source of error in sex determination using forensic multiplex kits. Issue 1 (December 2019) - Dunkelmann, Bettina; Helm, Katharina; Grießner, Ines; Zahrer, Waltraud; Müller, Eva; Kastinger, Tamara; Kreindl, Gabriele; Cemper-Kiesslich, Jan; Neuhuber, Franz
Abstract: In forensic genotyping the gender specific marker Amelogenin is a valuable tool for gender determination. This marker is therefore standard in all commercial forensic genetic kits. However, gonosomale aberrations, deletions or primer binding site mutations can cause problems in the correct interpretation of the marker Amelogenin and consequently a valid sex determination. Misleading results can be obtained based on incorrect interpretation of the phenotype or genetic intersexuality even though the genotyping based on Amelogenin itself was performed and evaluated correctly. In our routine casework we observed six cases with discrepancies regarding the biological and the "legal" gender. Further investigation of these cases revealed varying reasons for these discrepancies. But not all cases could be completely resolved and clarified.